Asuhan Keperawatan pasien dengan Chronic Kidney Disease (CKD) di Ruangan Interne RSUD Prof. H. Muhammad Yamin, SH Pariaman - Riska Julita Putri; Hilma Yessi; Mike Asmaria; Debby Silvia Dewi (CV. ITTC INDONESIA, 2026)
According to data from the World Health Organization (WHO), the number of Chronic Kidney Disease (CKD) cases in 2021 was recorded at more than 843.6 million. By 2025, this number is expected to reach around 850 million, with approximately 4 million individuals requiring renal replacement therapy. In Indonesia, the prevalence of CKD reaches 638,178 cases. Meanwhile, in West Sumatra, the prevalence is around 0.40% with a total of 13,834 cases. In Prof. H. Muhammad Yamin, SH Pariaman Regional General Hospital, CKD ranked first in 2025 with 335 cases. The purpose of this case study is to understand and apply nursing care to patients with Chronic Kidney Disease (CKD). The method used is a case study with a nursing process approach for one patient, Mr. E in the internal room of Prof. H. Muhammad Yamin, SH Pariaman Regional General Hospital on February 9-13, 2026. The results of the 5-day study showed nursing problems, namely: Hypervolemia, Ineffective Breathing Pattern, Ineffective Peripheral Perfusion, Acute Pain and Risk of Ineffective Renal Perfusion. Interventions and implementations carried out were hypervolemia management, airway management, circulation care, pain management, shock prevention anddisease process education. The author's suggestion is that patients can adopt a healthy lifestyle, such as limiting fluids, limiting foods high in sodium and potassium and routine hemodialysis to the hospital. In conclusion, after nursing care with CKD, the patient's condition showed improvement marked by reduced shortness of breath, edema, fatigue and pain.